Development and Fecundity of Oriental Fruit Moth (Lepidoptera: Tortricidae) Reared on Various Concentrations of Amygdalin - Yi Wang; Jie Li; Xiaohan Chai; Xuefeng Hu; Xianwei Li; Weina Kong; Ruiyan Ma (Insects, 2022)
Grapholita molesta (Busck) (Lepidoptera: Tortricidae), Oriental fruit moth (OFM), attacks fruits and shoots of the economically important trees in Rosaceae. Amygdalin is a cyanogenic glucoside of rosaceous plants that may be related to the seasonal patterns of infestation in many pests. The amygdalin concentration of fruits and shoots of peach, pear, and apple varies over the growing season. However, the relationship between the amygdalin concentration and G. molesta performance has not been reported. Here, we measured the performance (feeding, growth, development, and fecundity) of G. molesta larvae (as subsequent adults) reared on artificial diets with six amygdalin concentrations (0, 3, 6, 12, 24, and 48 mg/g), and we then calculated the population parameters. We found that these different concentrations of amygdalin affected the developmental time and fecundity, except for the proportion of larvae feeding on the diet and the survival rates of larvae and pupae. When compared with the control diet without amygdalin, diets with 3 or 6 mg/g (low and moderate concentrations) of amygdalin shortened developmental times and increased the number of eggs laid by females; however, a diet with 12 mg/g (moderate concentration) of amygdalin only increased the number of eggs laid by females and did not affect the larval and pupal developmental rate. A diet with 48 mg/g (high concentration) of amygdalin prolonged developmental times and reduced the number of eggs laid by females when compared with the control diet without amygdalin. Furthermore, the intrinsic rate of increase (rm) for insects reared on diets with 3 or 6 mg/g (low and moderate concentrations) of amygdalin versus the control diet without amygdalin showed a slightly improved population growth. However, this increase in the rm value did not persist over ten successive generations of rearing on the same diet. We concluded that the diet with 6 mg of amygdalin per g of diet can enhance the performance and population growth of G. molesta, but the effects of amygdalin are concentration-dependent.